Characterization and identification of programming languages - Alves, Júlio (2023)
This paper presents and discusses a research work whose main goal is to identify which characteristics influence the recognition and identification, by a programmer, of a programming language, specifically analysing a program source code and its linguistic style. In other words, the study that is described aims at answering the following questions: which grammatical elements – including lexical, syntactic, and semantic details – contribute the most for the characterization of a language? How many structural elements of a language may be modified without losing its identity? The long term objective of such research is to acquire new insights on the factors that can lead language engineers to design new programming languages that reduce the cognitive load of both learners and programmers. To elaborate on that subject, the paper starts with a brief explanation of programming languages fundamentals. Then, a list of the main syntactic characteristics of a set of programming languages, chosen for the study, is presented. Those characteristics outcome from the analysis we carried on at first phase of our project. To go deeper on the investigation we decided to collect and analyze the opinion of other programmers. So, the design of a survey to address that task is discussed. The answers obtained from the application of the questionnaire are analysed to present an overall picture of programming languages characteristics and their relative influence to their identification from the programmers’ perspective.